Workshop Penggunaan Quizizz Dalam Meningkatkan Pembelajaran Digital Dan Interaktif - Pujiastuti, Arum; Nurhidayah, Siti Abdillah; Ridhasyah, Rizki (Universitas Negeri Gorontalo, 2025)
Integrating technology into education has become essential in the digital era to enhance the quality of learning. However, many teachers face challenges such as limited knowledge, resources, and creativity in utilizing technology. This community service program aims to improve teachers' competencies through training on using Quizizz as an interactive teaching medium. The methods included developing a comprehensive training module, presentations, demonstrations, hands-on workshops, and a QA session. The results showed that most participants, comprising 37 teachers from SMP Negeri 1 Singorojo, found the training effective in helping them understand the concept of interactive teaching media and practice creating quizzes using Quizizz. Evaluations indicated positive outcomes, although participants suggested extending the workshop duration. This program offers practical solutions for teachers to design more creative, interactive, and relevant lessons while paving the way for further development of similar initiatives in the future.